Stress Management Strategies Among Women Police Officers in Kerala: Challenges and Opportunities - S, Linjiya; T.T., Arun Kumar (NPRC Journal of Multidisciplinary Research, 2025)
Women police officers in Kerala face unique stressors due to the demanding nature of law enforcement, societal expectations, and challenges in achieving work-life balance. Despite their critical contributions to public safety, the stress factors affecting women in the police force and the effectiveness of existing stress management practices remain underexplored. This study seeks to address this gap by identifying the key stress factors impacting women police officers in Kerala and evaluating the effectiveness of the stress management practices currently in place.The research highlights how occupational stress, role conflicts, exposure to traumatic events, and insufficient institutional support exacerbate the challenges faced by women officers. Findings from this study aim to contribute to the development of targeted interventions and policies to enhance the mental well-being and professional performance of women police personnel. This will ensure a more inclusive and supportive working environment, ultimately improving public service delivery.